"T2-high" in severe asthma related to blood eosinophil, exhaled nitric oxide and serum periostin. Issue 1 (3rd January 2019) - Pavlidis, Stelios; Takahashi, Kentaro; Ng Kee Kwong, Francois; Xie, Jiaxing; Hoda, Uruj; Sun, Kai; Elyasigomari, Vahid; Agapow, Paul; Loza, Matthew; Baribaud, Fred; Chanez, Pascal; Fowler, Steve J.; et al.
Type-2 (T2) immune responses in airway epithelial cells (AECs) classifies mild–moderate asthma into a T2-high phenotype. We examined whether currently available clinical biomarkers can predict AEC-defined T2-high phenotype within the U-BIOPRED cohort. The transcriptomic profile of AECs obtained from brushings of 103 patients with asthma and 44 healthy controls was obtained and gene set variation analysis used to determine the relative expression score of T2 asthma using a signature from interleukin (IL)-13-exposed AECs. 37% of asthmatics (45% nonsmoking severe asthma, n=49; 33% of smoking or ex-smoking severe asthma, n=18; and 28% mild–moderate asthma, n=36) were T2-high using AEC gene expression. They were more symptomatic with higher exhaled nitric oxide fraction ( F eNO ) and blood and sputum eosinophils, but not serum IgE or periostin. Sputum eosinophilia correlated best with the T2-high signature. F eNO (≥30 ppb) and blood eosinophils (≥300 cells·µL −1 ) gave a moderate prediction of T2-high asthma. Sputum IL-4, IL-5 and IL-13 protein levels did not correlate with gene expression. T2-high severe asthma can be predicted to some extent from raised levels of F eNO, blood and sputum eosinophil counts, but serum IgE or serum periostin were poor predictors. Better bedside biomarkers are needed to detect T2-high. T2-high was found in 45% of nonsmoking and 33% of smoking/ex-smoking severe asthma and 28% of mild–moderate asthma. This can be predicted from raised levels of nitric oxide in exhaled breath, blood and sputum eosinophil counts, but not from serum periostin. http://ow.ly/Zsq630myR9t